Investigating the shared genetic basis and causal relationships between mucosa-associated lymphoid tissue inflammation and psychiatric disorders - Georgiou, Andrea N.; Voskarides, Konstantinos; Zanos, Panos; Chatzittofis, Andreas (Frontiers in Psychiatry, 2024)
Background: Chronic and acute inflammation of the mucosa-associated lymphoid tissue have been positively linked to the development of psychiatric disorders in observational studies. However, it remains unclear whether this association is causal. In the present study, we investigated this association, using as proxies genetically predicted tonsillectomy, appendectomy and appendicitis on psychiatric disorders including major depressive disorder (MDD), schizophrenia (SCZ), bipolar depression (BD) and anxiety (ANX) via a two-sample Mendelian randomization (MR) analysis. Methods: Genetic association summary statistics for tonsillectomy, appendectomy and appendicitis were sourced from FinnGen Consortium, comprising data from 342,000 participants. Genetic correlations between all exposures and outcome were calculated with Linkage Disequilibrium Score (LDSC) Regression analysis. MR estimates were then calculated to assess their impact on the risk of developing psychiatric disorders. Sensitivity analysis was employed to test for any directional pleiotropy. Results: Our results suggest that there is no direct causal association between tonsillectomy, appendectomy or appendicitis with a heightened risk for development of psychiatric disorders. The robustness of the results of the main MR analysis was further confirmed with additional sensitivity analyses. However, a moderate inverse genetic correlation was observed between tonsillectomy and MDD traits (rg=-0.39, p-value (P)=7.5x10-5). Conclusion: Our findings provide, for the first time, evidence that there is no causal association between tonsillectomy or appendectomy on subsequent vulnerability of developing psychiatric disorders. Future studies using larger sample size GWAS should focus on unraveling the confounding factors and mediators to investigate this relationship further.